MINISTÉRIO PÚBLICO E EFETIVAÇÃO DE DIREITOS: Auxílio no combate à violência nas novas democracias latino-americanas - Anarda Pinheiro Araújo (Universidade Federal do Maranhão, 2009)
This article discusses the importance of public prosecutors to combat widespread violence in Latin America. First, the research refers to a brief history of democratic institutions, starting from the ancient Greece up to the new Latin American democracies. It highlights the attitude of Latin American citizens about the legitimacy and efficiency of democratic institutes as an answer to fight social inequality and its consequences, as the frightening increasing of violence. That done, it is necessary to amplify the concept about the concept of violence, crime rates in Latin America, the main victims and the performance of the police in criminal investigations. Finally, it is presented the Public Prosecutor’s Office on Latin America, focusing a preliminary study in the historical evolution of the institution in Brazil, and after that, the ministerial functions in other Latin countries. It is the need for the prosecutors action by in combating violence throughout Latin America, using primarily the legitimacy of their role in criminal investigations as an effective instrument in combating crime and protecting fundamental human rights that is presented in this paper.